THE TYPOLOGY OF APPLICATIVE/CAUSATIVE MARKING IN TAPUS - NFN Yanti; Tim McKinnon; Peter Cole; Gabriella Hermon (Linguistik Indonesia, 2021)
This paper constitutes an initial examination of the applicative/causative suffix -ge in Tapus, a divergent traditional Minangkabau variety spoken in rural Western Sumatra. Our aim is to show that the similarities and divergences from Standard Indonesian of traditional rural varieties provides insight into the properties of “Indonesian-type” languages in general. The distribution of applicatives/causatives in Tapus is interesting for several reasons. First, applicative/causative suffixes in Indonesian-type languages are well-known for the use of the same morphology for a variety of purposes. The fact that a single form is used for these different functions raises the question of whether the applicative/causative morphemes are two (or more) distinct morphemes or whether the form has a unitary linguistic function. We will show that the unitary analysis for causative and benefactive uses of the applicative/causative suffix cannot account for the data in Tapus. Another area of interest with regard to this suffix relates to constraints on movement.  We show that the Extreme Locality Hypothesis cannot account for the Tapus data based on the interaction between the applicative/causative suffix and information question formation/relativization. Finally, we demonstrate that Pylkkänen’s typology of applicatives makes incorrect predictions with respect to the interpretations available for benefactives in Tapus and other Indonesian-type languages, showing the necessity for an expanded taxonomy of applicative forms. Our general conclusion is that the detailed examination of grammatical constructions in divergent Malayic varieties leads to new and surprising insights into the grammatical profile of Indonesian-type languages.